2010
DOI: 10.1007/s10502-010-9112-3
|View full text |Cite
|
Sign up to set email alerts
|

British Colonial Administrations’ registry systems: a comparative study of Northern Rhodesia and Nyasaland

Abstract: Recordkeeping in twentieth century colonial states has been ignored by scholars, or at best regarded as the result of a monolithic process of migration of metropolitan practices. Registries provided the principal organ of recordkeeping in British government systems of administration. This comparative study of the registries in the neighbouring territories of Northern Rhodesia (now Zambia) and Nyasaland (now Malawi) reveals the true extent of metropolitan British influence, exposing an absence of centralised ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 13 publications
1
3
0
Order By: Relevance
“…… This comparative study … reveals … an absence of centralised advice, and a consequent dependence upon individual innovation. 2 Our study confirms the importance of innovation in Britain's overseas territories. Before moving on to address our main themes, however, it is necessary to say something about metropolitan practices and controls and to provide some historical background to colonial administration, so that what follows may be intelligible to the general reader.…”
Section: Recordkeeping In the Imperial Peripherysupporting
confidence: 79%
“…… This comparative study … reveals … an absence of centralised advice, and a consequent dependence upon individual innovation. 2 Our study confirms the importance of innovation in Britain's overseas territories. Before moving on to address our main themes, however, it is necessary to say something about metropolitan practices and controls and to provide some historical background to colonial administration, so that what follows may be intelligible to the general reader.…”
Section: Recordkeeping In the Imperial Peripherysupporting
confidence: 79%
“…This under-resourcing of archival work resulted in inadequate and unintegrated planning; a low skills base among personnel, inadequate records management in government ministries and departments and absence of clear career paths for staff (Kemoni and Ngulube, 2007, p. 123). The findings of research by scholars such as Kemoni and Ngulube (2007); Mnjama (2005) Keakopa (2007), Tough (2009) and Lovering (2010) point unambiguously to archival systems that are under severe strain in the ESARBICA region. The advent of electronic records in the region has also presented further challenges to the management and preservation of records.…”
Section: Introductionmentioning
confidence: 96%
“…As such, records are critical components of the process of accountability in the country. Tough (2009) and Lovering (2010) observed that the rise of electronic records within Southern region of Africa has ushered in varied challenges on how best to manage and preserve the records. Akotia (2003) share that implementing sound national system of archiving and managing records can play a serious role in alleviation of the limitations that come with national archives.…”
Section: Background To the Studymentioning
confidence: 99%